2018
DOI: 10.3389/fphar.2018.00726
|View full text |Cite
|
Sign up to set email alerts
|

4-(Hydroxymethyl)catechol Extracted From Fungi in Marine Sponges Attenuates Rheumatoid Arthritis by Inhibiting PI3K/Akt/NF-κB Signaling

Abstract: Rheumatoid arthritis (RA) is a progressive autoimmune disease specific to synovial joints; it causes joint damage and other systemic abnormalities, thereby leading to physical disability and early mortality. Marine sponge-derived fungi, Pestalotiopsis sp., secrete immunosuppressive compounds in the culture broth. In the present study, we isolated 4-(hydroxymethyl)catechol (4-HMC) from these fungal species, and evaluated its anti-RA effects using a murine collagen-induced arthritis model and tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Importantly, NF-κB is the key target of p38 MAPK and Akt signaling pathways after LPS binding TLR4/MYD88 to initiate intracellular pathways [11,12]. Both p38 MAPK/MK2 and PI3K-Akt can regulate LPS-induced gene expression by controlling NF-kB p65 hyperphosphorylation and nuclear translocation [47,48,49]. Here, our data showed that DHL pre-incubation suppressed NF-κB (p65) phosphorylation and nuclear translocation in LPS-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, NF-κB is the key target of p38 MAPK and Akt signaling pathways after LPS binding TLR4/MYD88 to initiate intracellular pathways [11,12]. Both p38 MAPK/MK2 and PI3K-Akt can regulate LPS-induced gene expression by controlling NF-kB p65 hyperphosphorylation and nuclear translocation [47,48,49]. Here, our data showed that DHL pre-incubation suppressed NF-κB (p65) phosphorylation and nuclear translocation in LPS-stimulated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the KEGG pathway analysis also indicated that PI3K-Akt, TNF, and IL-17 signaling pathway may be a critical signaling pathway in the network pharmacology. The PI3K-Akt signaling pathway is involved in inflammatory cytokine production [ 67 ], proliferation and migration of RAFLS [ 68 ] and chondrocyte proliferation [ 69 ], and apoptosis and autophagy in RA [ 69 ]. Moreover, a pivotal role for the proinflammatory cytokines, including tumor necrosis factor (TNF) [ 70 ] and interleukin- (IL-) 17 [ 71 ], in RA joint pathology has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…phenolics and benzoquinones derivatives (4-(Hydroxymethyl)-catechol and benzoquinone) modulate immune pathways such as PI3K/Akt/NF-κB, and STAT1 signaling; respectively [ 33 , 34 ]. Hydroxybenzoic acids such as gallic and vanillic acids promote differentiation of regulatory T-cells and enhance immune responses in murine models [ 35 , 36 ].…”
Section: Overview On Immunizations With Carrier-plant-phenolics Conjumentioning
confidence: 99%